METODE PEMAHAMAN MUHAMMAD SYAHRÛR TERHADAP AYAT-AYAT HUKUM - Syofrianisda Syofrianisda; Dewi Murni (Program Studi Ilmu Al-Qur’an dan Tafsir Fak. Ilmu Agama Islam Universitas Islam Indragiri, 2017)
Syahrûr as instigators of techniques can also be viewed as an observer of Islamic science, especially concerning the interpretation of legal verses of the famous al-hudud nazhariyyah theory (theoretical limit). Nazhariyyahal-Hudûd Muhammad Syahrûr is the ordinance of God against the limits of his terms in the Qur'an that should not be exceeded. The limit is there are six forms, namely the minimum limit, the maximum limits, maximum and minimum limits, minimum limits as well as maximum limits, maximum limits are close to straight lines and minimal restrictions that may be skipped but the maximum limit should not be skipped. Nazhariyyahal-Hudud foundation drawn from the word hudûd contained in the al-Quran al-Nisa 'verse 13, and in operational use Linguistic structuralism approach. This theory can be applied among others in the problems mahram who put in a minimum limit, the penalty of hand amputation for theft as the perpetrators of the maximum limit, the problem of polygamy in the position of minimum and maximum limits, penalty 100 times flogging for adultery as well as limit the maximum threshold, the physical relationship between men and women in positions close to the maximum limit straight line, and the permissibility of interest does not reach 100% is charged to those who have capital as the minimum limit that may be skipped and the maximum limits that should not be skipped.